Elvitegravir concentrations in seminal plasma in HIV‐1‐infected men1. Issue 3 (1st August 2016) - Imaz, A; Niubó, J; Kashuba, AD; Ferrer, E; Sykes, C; Rozas, N; Acerete, L; Vila, A; Podzamczer, D
Abstract : Objectives: The aim of the study was to quantify elvitegravir (EVG) concentrations in the semen of HIV‐1‐infected men receiving antiretroviral therapy (ART) consisting of an elvitegravir/cobicistat/emtricitabine/tenofovir (EVG/COBI/FTC/TDF) single‐tablet regimen. Methods: A phase IV, cross‐sectional study was carried out including HIV‐1‐infected male adults with suppressed plasma HIV‐1 RNA who switched ART to EVG/COBI/FTC/TDF. Total EVG concentrations at the end of the dosing interval ( C 24 h ) and HIV‐1 RNA were measured in paired seminal plasma (SP) and blood plasma (BP) samples 4 weeks after switching to EVG/COBI/FTC/TDF. Validated liquid chromatography−tandem mass spectrometry (LC‐MS/MS) was used to quantify EVG concentrations, and HIV‐1 RNA was determined by real‐time polymerase chain reaction (PCR). Results: Ten men were included. Their median age was 40 years (range 24–47 years), the median time on ART was 50 months (range 10–186 months), the median time with plasma HIV‐1 RNA < 40 copies/mL was 37 months (range 7–113 months), and the median CD4 count was 737 cells/μL (range 190–1122 cells/μL). Four weeks after switching to EVG/COBI/FTC/TDF, all subjects had HIV‐1 RNA < 40 copies/mL in both BP and SP. Median EVG C 24 h was 277 ng/mL (range 64.8–1790 ng/mL) in BP and 169 ng/mL (range 12.8–792 ng/mL) in SP. A significant correlation was observed between BP and SP EVG concentrations (Spearman rho 0.952; P < 0.001). The median SP:BP EVG concentration ratio was 0.39 (range 0.20–0.92). EVG C 24 h in SP was at least 23‐fold the in vitro protein‐unbound 50% effective response (EC50 ) of HIV‐1 clinical isolates (0.04–0.55 ng/mL). In all but one individual, EVG C 24 h in SP was also higher than the blood plasma protein binding‐adjusted 95% inhibitory concentration (IC95 ) of wild‐type HIV‐1 (45 ng/mL). Conclusions: Seminal EVG concentrations in HIV‐infected men treated with EVG/COBI/FTC/TDF sufficed to contribute to maintaining HIV‐1 RNA suppression in this compartment.